PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TARI BAMBU PADA MATA PELAJARAN SEJARAH - Desmawati, Desmawati (TABULARASA, 2014)
This study aims to determine whether the use of cooperative learning model bamboo dance can increase interest in studying history subjects. This type of research is